OMG: Organisasi UMKM Bersinergi sebagai Upaya Pemulihan Ekonomi di Tengah Keterbatasan Pandemi - Detia Zalyanti; Mhd Andika Wahyudi; Nugra Hani (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2021)
The era of economic disruption due to the Covid-19 pandemic has had a very drastic impact on the economy. The Indonesian economy in 2020 fell sharply, especially in the second quarter, at minus 5%, in contrast to 2019. One of the main factors was the shocking of the MSME sector as the largest contributor to Indonesia's GDP in previous years. The MSME sector is paralyzed, as evidenced by 68% of MSMEs discontinuing their operations, 65% of MSMEs choosing to temporarily stop their operations and another 3% permanently discontinuing them. In addition, market demand declined sharply, causing 4 out of 5 companies (80%) MSMEs to experience a significant decrease in income. The problems experienced by MSME actors during the pandemic include limitations and difficulties in obtaining capital, the absence of massive coordination between MSME actors, lack of creativity, knowledge and lack of motivation. The government has made efforts to overcome the rescue of MSMEs, by providing capital assistance funds of Rp. 2,400,000/UMKM, but with all the limitations, these efforts are not effective. The paralysis of the MSME sector as the largest contributor to GDP in Indonesia has hampered economic development in Indonesia. OMG: MSME ORGANIZATIONS SYNERGY BASED ON CROSS-COOPERATIONS AND ACHIEVEMENT AWARDING AS ECONOMIC RECOVERY EFFORTS IN THE MIDDLE OF PANDEMIC LIMITATIONS. The author believes that the presence of MSME organizations in synergy will help recovery efforts as well as economic development in the midst of limitations by raising and improving the quality of MSMEs in Indonesia. Thus, MSMEs will contribute to the maximum GDP contribution, which makes Indonesia's economic development much more advanced, both in the midst of the limitations of the pandemic and even after the pandemic.